Time as a constraint on group size in spider monkeys - Korstjens, A; Verhoeckx, I; Dunbar, R (Springer, 2006)
An animal can only survive in a given habitat if it has enough time to find, process and digest food whilst avoiding predation. The time it has for food acquisition is affected by the vegetation and competition with conspecifics, which depends on aggregation tendencies. We used the relationships between time allocations, on the one hand, and climatic variables (as a proxy for habitat quality) and group size, on the other, to develop a model that predicts maximum ecologically tolerable group size at different locations for spider monkeys. Spider monkeys are particularly interesting because the social communities often split up into small units. Temperature variation and rainfall variation were the main determinants of time budgets. Community size and average annual rainfall determined party size. The model correctly predicted presence or absence of spider monkeys at 78-83% of 217 New World forest sites. Within the geographical range of the species, this time budget model predicted the presence of spider monkeys better than a model based directly on climate variables. Predicted community and party sizes were significantly larger at sites where spider monkeys are present than at sites where they are absent. As required by the model, predicted maximum community sizes were significantly larger than observed community sizes. Moving time showed a U-shaped relationship with party size, which suggests that moving time is the factor that keeps spider monkey communities from travelling together in a tight group.